Mana-ā-kī(tanga) and Tourism in Aotearoa - Martin, Frances Kahui (Te Kaharoa, 2015)
The main focus of this article will discuss mana-ā-kī(tanga) and the tourism industry in Aotearoa (New Zealand). It will specifically investigate the interpretation of mana-ā-kī(tanga). Mana-ā-kī(tanga) does not discriminate between people and it is a selfless and unconditional act, with no preconceived expectations. I learned that mana-ā-kī(tanga) could be shared, not only amongst whānau (family) but also with manuhiri (visitor), including those from overseas. It is no wonder therefore that the term mana-ā-kī(tanga) is embraced and promoted within Aotearoa, to manuhiri from foreign shores. The term mana-ā-kī(tanga) is widely understood in the tourism industry as hospitality and reciprocity. Hence, possible misinterpretation of mana-ā-kī(tanga) could result in this concept being used incorrectly and lead to the transgression of cultural practices, thus compromising the experiences offered by Māori tourism operators. Throughout this article there is a deliberate emphasis on the spelling of mana-ā-kī(tanga) to show the importance of mana-ā-kī (respect earned from the recognition of others). Thus, the spelling in the English alphabet of manaakitanga and manaaki is used intermittently.